skn-1-Dependent and -Independent Regulation of aip-1 Expression following Metabolic Stress in Caenorhabditis elegans - Ferguson, Annabel A. (American Society for Microbiology (ASM), 2010)
Maintenance of a stable, properly folded, and catalytically active proteome is a major challenge to organisms in the face of multiple internal and external stresses which damage proteins and lead to protein misfolding. Here we show that internal metabolic stress produced by reactive intermediates resulting from tyrosine degradation triggers the expression of the aip-1 gene, which is critical in responses to the environmental toxin arsenic and the clearance of unstable polyglutamine and Aβ proteins. aip-1 acts via binding to the proteosome and enhancing proteosomal function. We find that full induction of aip-1 depends on the oxidative-stress-responsive skn-1 transcription factor but significant induction still occurs without skn-1. Importantly, activation of skn-1 with wdr-23(RNAi), which dramatically induces the expression of other skn-1 target genes, produces a minimal increase in aip-1 expression. This suggests that the previously demonstrated specificity in aip-1/AIRAP induction could reflect the actions of multiple synergistic activators, such as the heat shock factor homolog hsf-1, which we also find is required for full induction. These may be triggered by proteosome dysfunction, as we find that this event links the multiple inducers of aip-1. Together, our results show that cell stress triggers aip-1 expression by both skn-1-dependent and -independent pathways.